(untitled) (Educação e Pesquisa, 2003)
The text describes a study about the adoption of virtual learning environments and its consequences to the learning process of undergraduate students at the State University of Campinas - Unicamp. These environments can be incorporated in various ways into the academic daily life of students and teachers. One efficient way to promote the adoption of these environments, as observed by the Distance Learning support team, is to train teachers and students in their use. Two training alternatives are described in this text to instruct the academic community in the use of TelEduc, a freeware developed and coordinated by the NIED - Núcleo de Informática Aplicada à Educação (Center for Information Technology Applied to Education), and officially adopted by Unicamp. Training courses are offered in two ways - presence or distance learning - to suit each teacher's preferences. This article compares the two modes of training, showing their strong and weak points. The adoption of TelEduc and its direct consequences to the learning process are described in a study carried out with some engineering undergraduates at Unicamp. The authors' questions and the general views of teachers and students regarding the effectiveness of the use of TelEduc as a supporting tool to presence teaching are presented. This investigation revealed the importance of training teachers in the effective use of these environments.